A systematic review of the transformation of Lake Beseka from brine to nearly fresh lake water - Yosef Abebe; Taye Alemayehu; Bizuneh Asfaw Abebe; Tena Alamirew; Beteley Teckola; Esayas Alemayehu (Discover Sustainability)
Abstract Anthropogenic and hydrogeological factors are detrimental factors on the then brine lake, Beseka. The lake is in a state of dramatic change in its nature. The aim of this systematic review is to identify knowledge gaps related to the change in water quality and its suitability for different uses. The study also assesses trends in Lake Beseka's (LB) water quality. Previously, it was believed that volcanic lakes were harmful to the environment and unusable for the welfare of humans, animals, and other living things. However, LB in Ethiopia is a special or uncommon case to leave doubt to this general believes. This assessment shows the rapid transformation of the lake’s waters to safer and usable one from its brine form. To evaluate the water quality of Lake Beseka, various parameters and techniques (indices) can be used. Between 1961 and 2021, the lake’s salinity decreased from 74100 to 2520 µS/cm (1,654 µS/cm in April, 2024). Other important Water Quality Index parameters that show sharp decline can be mentioned. Sodium content declined from 17,800 to 630 mg/L, chlorides declined from 5480 to 210 mg/L, and sulfates, declined from 4680 to 192 mg/L. Eutrophication-related lake issues are being evaluated. Large-scale water quality parameters demonstrate rapid alterations brought on by freshwater discharge into lakes, which may shed light on their use for livestock and crop production. Although it is not currently advised for use, it has demonstrated an unpredicted dilution trend and is getting close to the FAO standards. It is crucial to take into account options to lessen the effects of the adjacent Awash River by upgrading infrastructure and changing the lake's natural flow in order to address the issues with average water quantity. As a result, the Lake Beseka water source will continue to be a useful resource for many years to come. This study suggests that volcanic lakes, such as Lake Beseka, may be crucial in addressing future water security issues in the basin.